Development of health promotion model for the elderly through community participation in Khok Sung Subdistrict, Mueang District, Nakhon Ratchasima Province - Bonkhunthod, Punnathut; Suebsoontorn, Wiraporn; Futrakul, Sirintra; Choojan, Saowanee; Sodkoksung, Vilairut (Disease Control Journal, 2025)
This study aimed to analyze the health status and quality of life of older adults in Khok Sung Subdistrict, Mueang District, Nakhon Ratchasima Province; to develop a community participatory health promotion model; and to evaluate the key success factors of the implementation. The research employed a Participatory Action Research (PAR) design based on the conceptual framework of Cohen and Uphoff. The sample consisted of 150 participants, including 60 older adults, 45 caregivers, and 45 community stakeholders. Quantitative data were collected using questionnaires, while qualitative data were obtained through focus group discussions and in-depth interviews. Quantitative data were analyzed using descriptive statistics and paired t-tests, and qualitative data were analyzed using content analysis. The findings revealed that the quality of life and overall health of older adults significantly improved after the implementation (p<0.05). The developed health promotion model comprised four stages: 1) situation and needs assessment, 2) participatory planning with the community and network partners, 3) capacity-building activities and local health innovation development, and 4) monitoring and evaluation. The network partners reported a high level of satisfaction with the program (mean=4.27, SD=0.60). Key success factors included proactive leadership within the community, continuous support from local administrative organizations, and collaboration among all relevant sectors.